KAJIAN LITERATUR FAKTOR – FAKTOR RISIKO PSIKOSOSIAL DI SEKTOR KONSTRUKSI SAAT PANDEMI COVID-19 - Angelica Savitrie Joanna; Dadan Erwandi (Universitas Pahlawan, 2022)
The World Health Organization (WHO) on March 9, 2020, has determined the status of the COVID-19 corona virus outbreak as a global pandemic. During the COVID-19 pandemic, the construction sector operates 100% without restrictions. This causes workers in the construction sector not only to have a profound effect on physical health but also mental health. According to WHO, fear and anxiety about COVID-19 disease and other factors can affect work stress (WHO, 2020). This research method uses the Preferred Reporting Items for Systematic Reviews & Meta-Analysis (PRISMA) method which discusses construction and psychosocial factors in the construction sector. The factors found to be the most dominant in the literature review were stress and fatigue, family-work conflict, interpersonal relationships, work demands, work organization (job control), and working hours. Stress and fatigue can be both factors and effects that affect the state and performance of workers. These factors arise because the construction business process is so dense and has targets that must be pursued every time and demands from high management during the COVID-19 pandemic. During the Pandemic, the timeline changes and the pressure on their workers is to the point where they must pawn the safety of the workers to meet the predetermined time limit as if this was done under normal circumstances. Keyword : Risk Factors, Construction Sector, Psychosocial Factors, COVID-19 Pandemic